Nucleant layer effect on nanocolumnar ZnO films grown by electrodeposition - Reyes Tolosa, María Dolores (2013)
Different ZnO nanostructured films were electrochemically grown, using an aqueous solution based on ZnCl2, on three types of transparent conductive oxides grow on commercial ITO (In2O3:Sn)-covered glass substrates: (1) ZnO prepared by spin coating, (2) ZnO prepared by direct current magnetron sputtering, and (3) commercial ITO-covered glass substrates. Although thin, these primary oxide layers play an important role on the properties of the nanostructured films grown on top of them. Additionally, these primary oxide layers prevent direct hole combination when used in optoelectronic devices. Structural and optical characterizations were carried out by scanning electron microscopy, atomic force microscopy, and optical transmission spectroscopy. We show that the properties of the ZnO nanostructured films depend strongly on the type of primary oxide-covered substrate used. Previous studies on different electrodeposition methods for nucleation and growth are considered in the final discussion.